Sex- and age-dependent effects of chronic corticosterone exposure on depressive-like, anxiety-like, and fear-related behavior: Role of amygdala glutamate receptors in the rat - Bertholomey, Megan L.; Nagarajan, Vidhya; Smith, Dana M.; Torregrossa, Mary M. (Frontiers in Behavioral Neuroscience, 2022)
Persistent glucocorticoid elevation consistent with chronic stress exposure can lead to psychopathology, including mood and anxiety disorders. Women and stress-exposed adolescents are more likely to be diagnosed with mood disorders, suggesting that sex and age are important factors in determining vulnerability, though much remains to be determined regarding the mechanisms underlying this risk. Thus, the aim of the present experiments was to use the chronic corticosterone (CORT) exposure paradigm, a model of depression-like behavior that has previously been established in primarily adult males, to determine the mood-related effects of CORT in female and adolescent rats. Depression- and anxiety-like effects in adulthood were determined using the sucrose preference (SPT), the forced swim test (FST), the elevated plus maze, and fear conditioning. Basolateral amygdala (BLA) and medial prefrontal cortex (mPFC) glutamate receptor subunit levels were then measured. In a subsequent experiment, adult male and female rats were tested for the effects of pharmacological activation (via AMPA) or inhibition (via NBQX) of AMPA receptors in the BLA on behavior in the FST. Overall, females showed reduced anxiety- and depressive-like behaviors relative to males. However, females treated with CORT in adolescence, but not adulthood, had increased immobility in the FST, indicative of depression-like behavior. In contrast, CORT did not alter behavior in adolescent-treated males, though the previously reported depression-like effect of adult CORT exposure was observed. Control females had higher expression of the AMPA receptor subunits GluA1 and GluA2/3 selectively in the BLA relative to males. Adolescent CORT treatment, however, decreased BLA GluA1 and GluA2/3 expression in females, but increased expression in males, consistent with the direction of depression-like behavioral effects. Male and female rats also demonstrated opposing patterns of response to BLA AMPA receptor modulation in the FST, with AMPA infusion magnifying the sex difference of decreased immobility in females. Overall, these experiments show that increased glutamate receptor function in the BLA may decrease the risk of developing depressive-like behavior, further supporting efforts to target glutamatergic receptors for the treatment of stress-related psychiatric disorders. These findings also support further focus on sex as a biological variable in neuropsychiatric research.